2017
DOI: 10.2147/por.s126509
|View full text |Cite
|
Sign up to set email alerts
|

Parental opinions regarding an opt-out consent process for inpatient pediatric prospective observational research in the US

Abstract: ObjectiveTo explore parental opinions regarding opt-out consent for inpatient pediatric prospective observational research in the US.Study designA series of handouts describing hypothetical observational research studies with opt-out consent were reviewed by parents of hospitalized children. A verbal survey explored parental opinions about the proposed consent process.ResultsA total of 166 parents reviewed the handout and completed the survey. Only 2/166 parents (1.2%) objected to the study described and anoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…These findings support previous research that identified parent preference of opt-out consent in biobanking [ 42 ]. This survey moves beyond another to note that parents preferred opt-out (or no consent) over other processes, rather than simply not voicing an objection, [ 48 ]. This coincides with a recent systematic review that suggested that no consensus exists on the most appropriate consent for biobanks [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings support previous research that identified parent preference of opt-out consent in biobanking [ 42 ]. This survey moves beyond another to note that parents preferred opt-out (or no consent) over other processes, rather than simply not voicing an objection, [ 48 ]. This coincides with a recent systematic review that suggested that no consensus exists on the most appropriate consent for biobanks [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Because parents were not asked to compare or even consider other consent processes, this perceived acceptability of opt-out consent for biobanking is incomplete. In another study, 166 parents of children in pediatric wards were surveyed about consent preferences for hypothetical observational research [ 48 ]. Fifty-two percent chose an opt-in consent approach, 33% selected opt-out, and about 15% felt that consent was unnecessary [ 48 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[33] In the USA, researchers avoided this situation by checking with attending clinicians about parental distress and the stability of the child's condition. [34] With this safeguard, only two of 166 parents objected to opt-out consent. It was concluded that opt-out consent was acceptable and family-friendly if parents' questions could be answered.…”
Section: The Views Of Parents Children and Young Peoplementioning
confidence: 99%